Eukaryotic microalgae-bacteria synthetic consortia boost crop productivity and drought tolerance in bread wheat (Triticum aestivum) - Molina-Favero, Celeste; Sanchez Rizza, Lara; Gonzalez Olano, Angie Melissa; Maroniche, Guillermo; Polizzi, Mauro; de Gerónimo, Eduardo; Creus, Cecilia; Curatti, Leonardo; Pagnussat, Luciana Anabella (Frontiers in Plant Science, 2026)
Wheat provides the main source of nourishment for more than 40% of the global population, making it an essential crop. The challenge of overseeing crop management to guarantee water efficiency has been enhanced by the increase in rainfall unpredictability caused by climate change. Plant-growth-promoting bacteria (PGPBs) are beneficial microorganisms capable of improving crop yield and adaptability to environmental stresses. Single-celled eukaryotic algae, on the other hand, are comparatively understudied organisms that exhibit plant-biostimulant properties. Our research demonstrates that co-inoculation of Azospirillum argentinensis Az39 with the microalgae Scenedesmus obliquus C1S increases bacterial root colonization and the sole inoculation with microalgae improves germination and post-germinative growth under drought conditions. Field trials conducted on 2022 and 2024, under the influence of environmental drought conditions, revealed a 36% boost in grain yield and a 26.2% improvement in crop water productivity resulting from inoculation with microalgae-PGPB consortia. Moreover, under induced drought conditions, seedlings inoculated with microalgae showed a 50% increase in root dry weight. Notably, our results also reveal that inoculation efficiency was affected by tillage methods. The findings presented herein disclose a promising potential for the development of a novel eukaryotic microalgae-PGPB synthetic consortia inoculant that enhances root colonization by PGPBs and improves wheat crop water productivity in the field.